EVALUASI TERHADAP PELAKSANAAN TUGAS TATA USAHA MADRASAH ALIYAH NEGERI 3 BANJARMASIN - hermawan, Ade (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
The implementation of the administrative work of Madrasah Aliyah Negeri 3 Banjarmasin in the field of personnel administration, financial administration, infrastructure administration, public relations administration, archive administration, and student administration is in good category. Overall there are 67% of respondents who answered that the administrative service was good, 31% answered quite well, and 2% answered less well. This means that it can be concluded that the implementation of the administrative work of Madrasah Aliyah Negeri 3 Banjarmasin is good.